2013
DOI: 10.1186/1471-244x-13-202
|View full text |Cite
|
Sign up to set email alerts
|

Biological and other health related correlates of long-term life dissatisfaction burden

Abstract: BackgroundMental health is interconnected with somatic health and can manifest itself in biological processes. Life dissatisfaction is an indicator of subjective well-being, but information on its biological correlates is scarce. The aim of this study was to investigate the biological correlates along with other health-related factors of long-term life dissatisfaction in a population-based sample.MethodsAs part of the Kuopio Depression Study, health questionnaires were sent to a randomly selected population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the first exploration of the associations of both sleep duration and sleep quality with self-rated health in a sample of elderly individuals. Since this is the first of such studies, our results were explained in the highlights of similar studies [27,28]. Specifically, Paunio et al [27] and Rissanen et al [28] showed that 'poor' sleep quality was associated with 'poor' life satisfaction in the general population.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To the best of the authors' knowledge, this is the first exploration of the associations of both sleep duration and sleep quality with self-rated health in a sample of elderly individuals. Since this is the first of such studies, our results were explained in the highlights of similar studies [27,28]. Specifically, Paunio et al [27] and Rissanen et al [28] showed that 'poor' sleep quality was associated with 'poor' life satisfaction in the general population.…”
Section: Discussionmentioning
confidence: 57%
“…Since this is the first of such studies, our results were explained in the highlights of similar studies [27,28]. Specifically, Paunio et al [27] and Rissanen et al [28] showed that 'poor' sleep quality was associated with 'poor' life satisfaction in the general population. Our results could be explained by the fact that life satisfaction was strongly associated with self-rated health in previous studies [29].…”
Section: Discussionmentioning
confidence: 57%
“…Adiponectin activity is strongly associated with metabolic disorders and energy expenditure interactions, but it has also been associated with various mental disorders such as mood disorders, anxiety disorders, eating and sleep Decreased serum adiponectin levels have been also reported in major depressive disorders, panic disorders and schizophrenia [41][42][43] . Serum levels of adiponectin were significantly lower in elderly patients with major depressive disorders than in non-depressed controls [44,45] . Adiponectin also plays an important role in depression-related behaviors.…”
Section: Adiponectin In Mental Disordersmentioning
confidence: 83%
“…In one of the first studies, Hamer and Chida (2011) found that life satisfaction predicted lower CRP levels in the Scottish Health Survey (also see Nowakowski, 2014). However, the population-based Kuopio Depression Study did not find life satisfaction to be significantly related to either IL-6 or CRP, although it was related to higher levels of the anti-inflammatory adipokine adiponectin (Rissanen et al, 2013). Although more work is needed using a broader panel of inflammatory markers, results of the current study are important because CRP and IL-6 are robust predictors of future cardiovascular risk (Bisoendial et al, 2010; Libby et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Two important markers of inflammation include interleukin-6 (IL-6) and C-reactive protein (CRP) which predict future risk for cardiovascular disease and related mortality (Bisoendial, Boekholdt, Vergeer, Stroes, & Kastelein, 2010; Hunter & Jones, 2015; O Hartaigh et al, 2013). To date, only three studies appear to have tested the link between life satisfaction and inflammation: Two have found life satisfaction to predict lower CRP and IL-6 levels (Hamer & Chida, 2011; Nowakowski, 2014) while the other study did not (Rissanen et al, 2013). Thus, more research is needed modeling these inflammatory biological pathways.…”
mentioning
confidence: 99%